2021
DOI: 10.1016/j.bioactmat.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The construction of a lymphoma cell-based, DC-targeted vaccine, and its application in lymphoma prevention and cure

Abstract: In recent years, Non-Hodgkin lymphoma (NHL) has been one of the most fast-growing malignant tumor diseases. NHL poses severe damages to physical health and a heavy burden to patients. Traditional therapies (chemotherapy or radiotherapy) bring some benefit to patients, but have severe adverse effects and do not prevent relapse. The relevance of emerging immunotherapy options (immune-checkpoint blockers or adoptive cellular methods) for NHL remains uncertain, and more intensive evaluations are needed. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…To overcome this problem, new studies have been performed for immunotherapy alone or combined with chemotherapy by using nanotechnology. Vaccine studies are also frequently investigated in this area [ 99 , 100 ]. Notably, there are several studies with CpG, which is used as vaccine adjuvant to target lymph nodes in the literature.…”
Section: Nano-immunotherapy Applications In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, new studies have been performed for immunotherapy alone or combined with chemotherapy by using nanotechnology. Vaccine studies are also frequently investigated in this area [ 99 , 100 ]. Notably, there are several studies with CpG, which is used as vaccine adjuvant to target lymph nodes in the literature.…”
Section: Nano-immunotherapy Applications In Cancer Treatmentmentioning
confidence: 99%
“…For this purpose, the vaccine was combined with the anticancer drug doxorubicin. The combined system showed stronger antitumoral efficacy compared to chemotherapy and immunotherapy [ 100 ]. In another study, the efficiency of PEG-Fmoc-NLG (PEG-derivatized NLG919) micelles loaded with doxorubicin in lymphoma was investigated.…”
Section: Nano-immunotherapy Applications In Cancer Treatmentmentioning
confidence: 99%
“…[4][5] However, the damage of chemotherapy or radiotherapy to the body is very serious. [6][7][8] As a result, a less toxic therapeutic method that can be used in combination with immunotherapy is critical. Studies have shown that regulating metabolism to treat tumors is therapy with fewer side effects and significant therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these immunotherapy strategies have been adopted in clinical practices and demonstrated to be efficacious for cancer diseases. The emergence of new therapeutic targets [ 1 , 8 , 9 ] or new strategies [ [10] , [11] , [12] ] to improve the efficacy and reduce the side effect of immunotherapy are becoming attractive in cancer treatment. However, since tumor immunity is a complex process that is not fully understood yet, this emerging immunotherapy is facing great challenges such as a low targeting efficacy, which would reduce the therapeutic effect of administrated drugs, and intrinsic toxicities of immunotherapeutic drugs, which could cause severe inflammatory and autoimmune diseases [ [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%